A network meta-analysis protocol of conservative interventions for urinary incontinence in postpartum women. Issue 33 (14th August 2020) - Wang, Yang; Li, Hui; Wang, Jun; Hao, Qinghong; Tu, Yang; Chen, Yalin; Qiu, Mimi; Peng, Wei; Liu, Yunlu; Zhu, Tianmin
Abstract: Background: Postpartum urinary incontinence (PPUI) is a common urological condition in women after childbirth. Due to the side effects of surgical and pharmacological therapies, the patients and physicians alike express a strong preference for conservative approaches on PPUI, such as pelvic floor muscle training, biofeedback, electrical stimulation, bladder training, vaginal cones and acupuncture. Application of these conservative approaches should be guided by high quality evidence, yet their comparative effectiveness has not been well documented. Therefore, the network meta-analysis aims to compare, rank and summarize all available studies to determine which conservative intervention is more effective for PPUI. Methods: In this present study, qualified English and Chinese studies will be searched in PubMed, Scopus, EMBASE, The Cochrane Library, Web of Science, VIP Database, Wanfang Database, Chinese Biomedical Literature Database and China National Knowledge Infrastructure. All eligible randomized controlled trails (RCTs) of conservative interventions for PPUI will be included. R software 3.61 (R Foundation for Statistical Computing, Vienna, Austria) will be applied to synthesize data and conduct network meta-analysis. I 2 statistic and Z test will be used to assess heterogeneity and inconsistency, respectively. Results: Ethical approval is not required for this existed literature based meta-analysis. The findings of this research will be disseminated through a recognized journal. Conclusion: The findings of this study will provide ranking evidence for clinicians and patients to choose a more appropriate conservative therapy on PPUI. Trial registration number: PROSPERO CRD42020168042